(untitled) (European Journal of Pure and Applied Mathematics, 2011)
In this paper, Numerical solution of Partial Diferential-Algebraic Equations(PDAEs) is considered by Multivariate Padè Approximations. We applied these method to one example. First Partial Diferential-Algebraic Equation(PDAE) has been converted to power series by two-dimensional differential transformation,Then the numerical solution of equation was put into Multivariate Padè series form. Thus we obtained numerical solution of Partial Diferential-Algebraic Equation(PDAE).